Poor Basic Sanitation Impact on Diarrhea Cases in Toddlers - Dian Prasasti Kurniawati; Shintia Yunita Arini; Isas Awwalina; Nala Astari Pramesti (Universitas Airlangga, 2021)
Introduction: Diarrhea is a disease associated with poor people and mostly suffered by toddlers. The poor environmental quality triggers the growth of pathogenic microorganisms. This study aimed to analyze the relationship between basic sanitation with diarrhea in toddlers. Methods: The study was observational analytical study with cross-sectional design. The study was conducted in Leran Village, Bojonegoro, East Java, Indonesia. The sample was toddlers mother, amounting 63 respondents choosing by simple random sampling technique. Results and Discussion: The results of data analysis showed that diarrhea in toddlers was related to the type of floor (p = 0.026, PR = 2.21), latrine condition (p = 0.000, PR = 3.28), waste management (p = 0.000, PR = 27.5), clean water source (p = 0.000, PR =5.32). Conclusion: Several ways to reduce the prevalence of diarrhea including cleaning the floor regularly, providing a mat on the floor, provide a closed and waterproof trash, boiled water before drinking, and washing hands with soap after contacting with the ground.